Variceal Hemorrhage: Decompression, Obliteration, or Both? - McCafferty, Benjamin J.; El Khudari, Husamedin; Salei, Aliaksei; Gunn, Andrew J. (Digestive Disease Interventions, 2022)
Variceal hemorrhage is a morbid condition that frequently mandates the involvement of interventional radiology to achieve successful and sustained hemostasis. Primary image-guided therapies for variceal hemorrhage include a transjugular intrahepatic portosystemic shunt and transvenous obliteration. Knowledge of variceal pathophysiology and anatomy, current techniques, and the evidence supporting therapeutic selection is paramount to successful patient outcomes. The purpose of this review is to provide the reader a framework of the available literature on image-guided management of bleeding varices to assist in clinical management.
Keywords: portal hypertension; variceal hemorrhage; transjugular intrahepatic portosystemic shunt; balloon-occluded retrograde transvenous obliteration; cirrhosis